60Fe in core-collapse supernovae and prospects for X-ray and gamma-ray detection in supernova remnants. Issue 3 (22nd February 2019) - Jones, Samuel W; Möller, Heiko; Fryer, Chris L; Fontes, Christopher J; Trappitsch, Reto; Even, Wesley P; Couture, Aaron; Mumpower, Matthew R; Safi-Harb, Samar
Abstract: We investigate 60 Fe in massive stars and core-collapse supernovae focussing on uncertainties that influence its production in 15, 20, and 25 M stars at solar metallicity. We find that the 60 Fe yield is a monotonic increasing function of the uncertain 59 Fe( n, γ) 60 Fe cross-section and that a factor of 10 reduction in the reaction rate results in a factor of 8–10 reduction in the 60 Fe yield, while a factor of 10 increase in the rate increases the yield by a factor of 4–7. We find that none of the 189 simulations we have performed are consistent with a core-collapse supernova triggering the formation of the Solar system, and that only models using 59 Fe( n, γ) 60 Fe cross-section that is less than or equal to that from NON-SMOKER can reproduce the observed 60 Fe/ 26 Al line flux ratio in the diffuse interstellar medium. We examine the prospects of detecting old core-collapse supernova remnants (SNRs) in the Milky Way from their gamma-ray emission from the decay of 60 Fe, finding that the next generation of gamma-ray missions could be able to discover up to ∼100 such old SNRs as well as measure the 60 Fe yields of a handful of known Galactic SNRs. We also predict the X-ray spectrum that is produced by atomic transitions in 60 Co following its ionization by internal conversion and give theoretical X-ray line fluxes as a function of remnant age as well as the Doppler and fine-structure line broadening effects. The X-ray emission presents an interesting prospect for addressing the missing SNR problem with future X-ray missions.